Implementasi Penggunaan Media Word Wall Dalam Meningkatkan Hasil Belajar Siswa Di Sb Kampung Bharu Kuala Lumpur Malaysia - Iskarimah, Rizqi Iskarimah; Tio Heriyana; Hermawan; Oman Hadiana; Hana Astria Nur (PGSD Universitas Muhammadiyah Cirebon, 2025)
Many students currently do not fully follow the learning optimally, due to the lack of media in learning that can improve student learning outcomes. Therefore, an interactive media is needed that can form student enthusiasm in Science subjects. One of the interactive learning media that can be used is wordwall media. Therefore, the researcher has the aim of knowing the learning outcomes of students when using wordwall media. The research approach used in this study is the quantitative method. With a one group pretest-posttest design research design. Judging from the results of the calculations above which indicate the relationship between the pretest and posttest that have been carried out, even the Sig. (2-tailed) value or the results of the paired samples Test value of 0.000 which we know if the significance level is below 0.05; then it is stated that there is an effect of the test treatment on the results of the pretest and posttest tests. Because 0.000 is below 0.050, it can be concluded that H0 is rejected and Ha is accepted. So by using this media it can affect student learning outcomes.